The triumph of provocation - Mackiewicz, Józef (Yale University Press, 2009)
This political treatise examines the history and nature of Communism as it developed in the Soviet Union and in Poland. The author argues that accommodation with the Communists simply helped them to impose their vision of the world and pursue their goal of global domination.